Assessment of intensity, prevalence and duration of everyday activities in Swiss school children: a cross-sectional analysis of accelerometer and diary data - Sennhauser Felix H; Ruch Nicole; Mäder Urs; Grize Leticia; Bringolf-Isler Bettina; Braun-Fahrländer Charlotte (BMC, 2009)
Abstract Background Appropriately measuring habitual physical activity (PA) in children is a major challenge. Questionnaires and accelerometers are the most widely used instruments but both have well-known limitations. The aims of this study were to determine activity type/mode and to quantify intensity and duration of children's everyday PA by combining information of a time activity diary with accelerometer measurements and to assess differences by gender and age. Methods School children (n = 189) aged 6/7 years, 9/10 years and 13/14 years wore accelerometers during one week in winter 2004 and one in summer 2005. Simultaneously, they completed a newly developed time-activity diary during 4 days per week recording different activities performed during each 15 min interval. For each specific activity, the mean intensity (accelerometer counts/min), mean duration per day (min/d) and proportion of involved children were calculated using linear regression models. Results For the full range of activities, boys accumulated more mean counts/min than girls. Adolescents spent more time in high intensity sports activities than younger children (p < 0.001) but this increase was compensated by a reduction in time spent playing vigorously (p = 0.04). In addition, adolescents spent significantly more time in sedentary activities (p < 0.001) and accumulated less counts/min during these activities than younger children (p = 0.007). Among moderate to vigorous activities, children spent most time with vigorous play (43 min/day) and active transportation (56 min/day). Conclusion The combination of accelerometers and time activity diaries provides insight into age and gender related differences in PA. This information is warranted to efficiently guide and evaluate PA promotion.